Dipeptidyl Peptidase 4 Inhibition Alleviates Shortage of Circulating Glucagon-Like Peptide-1 in Heart Failure and Mitigates Myocardial Remodeling and Apoptosis via the Exchange Protein Directly Activated by Cyclic AMP 1/Ras-Related Protein 1 Axis. (January 2016) - Aoyama, Morihiko; Kawase, Haruya; Bando, Yasuko K.; Monji, Akio; Murohara, Toyoaki
Abstract : Background—: Ample evidence demonstrates cardiovascular protection by incretin-based therapy using dipeptidyl peptidase 4 inhibitor (DPP4i) and glucagon-like peptide-1 (GLP-1) under either diabetic or nondiabetic condition. Their action on myocardium is mediated by the cyclic AMP (cAMP) signal; however, the pathway remains uncertain. This study was conducted to address the effect of DPP4i/GLP-1/cAMP axis on cardiac dysfunction and remodeling induced by pressure overload (thoracic aortic constriction [TAC]) independently of diabetes mellitus. Methods and Results—: DPP4i (alogliptin, 10 mg/kg per day for 4 weeks) prevented TAC-induced contractile dysfunction, remodeling, and apoptosis of myocardium in a GLP-1 receptor antagonist (exendin [9-39])–sensitive fashion. In TAC, circulating level of GLP-1 (in pmol/L; 0.86±0.10 for TAC versus 2.13±0.54 for sham control) unexpectedly declined and so did the myocardial cAMP concentration (in pmol/mg protein; 33.0±1.4 for TAC versus 42.2±1.5 for sham). Alogliptin restored the decline in the GLP-1/cAMP levels observed in TAC, thereby augmented cAMP signaling effectors (protein kinase A [PKA] and exchange protein directly activated by cAMP 1 [EPAC1]). In vitro assay revealed distinct roles of PKA and EPAC1 in cardiac apoptosis. EPAC1 promoted cardiomyocyte survival via concomitant increase in B cell lymphoma-2 (Bcl-2) expression and activation of small G protein Ras-related protein 1 (Rap1) in a cAMP dose–dependent and PKA–independent fashion. Conclusions—: DPP4i restores cardiac remodeling and apoptosis caused by the pathological decline in circulating GLP-1 in response to pressure overload. EPAC1 is essential for cardiomyocyte survival via the cAMP/Rap1 activation independently of PKA. Abstract : Supplemental Digital Content is available in the text.